Concept maps as a didactic and evaluative tool in teacher education for Physics students (Research, Society and Development, 2023)
The use of concept maps as an auxiliary tool in teaching various subjects has grown significantly, both in basic education and in undergraduate and postgraduate university courses. These maps aim to represent significant relationships between concepts through propositions, providing a schematic resource that encompasses a set of conceptual meanings inserted in the structure of these propositions. In the educational context, concept maps play a multifunctional role. As teaching tools, they can elucidate the hierarchical relationships between the concepts covered in a class, study unit or complete course. Furthermore, they serve as valuable resources to facilitate understanding and memorization, making the learning process more accessible and effective. As an assessment method, concept maps play a crucial role in helping to identify evidence of student learning in relation to the concepts of a given topic. By analyzing the quality and complexity of the maps created by students, it is possible to evaluate not only the knowledge acquired, but also the ability to relate and organize information in a coherent way. In this context, the present work aims to present the conceptual map as a fundamental teaching tool in the context of an undergraduate physics course. Given the qualitative and quantitative nature of this study, this work seeks to explore the potential of the map as a content evaluation tool. The aim is to contribute to a more comprehensive and efficient approach to the teaching and learning process.